A hydrogeomorphic assessment of twenty‐first century floods in the UK. Issue 2 (23rd November 2015) - Foulds, Simon A.; Macklin, Mark G.
Abstract: The occurrence of devastating floods in the British uplands during the first two decades of the twenty‐first century poses two key questions: (1) are recent events unprecedented in terms of their frequency and magnitude; and (2) is climate and/or land‐use change driving the apparent upturn in flooding? Conventional methods of analysing instrumental flow records cannot answer these questions because upland catchments are usually ungauged, and where records do exist they rarely provide more than 30–40 years of data. In this paper we analyse all lichen‐dated upland flood records in the United Kingdom (UK) to establish the longer‐term context and causes of recent severe flooding. Our new analysis of torrential sedimentary deposits shows that twenty‐first century floods are not unprecedented in terms of both their frequency (they were more frequent before 1960) and magnitude (the biggest events occurred during the seventeenth–nineteenth centuries). However, in some areas recent floods have either equalled or exceeded the largest historical events. The majority of recent floods have been triggered by torrential summer downpours related to a marked negative phase of the summer North Atlantic Oscillation (NAO) between 2007 and 2012. It is of concern that historical data suggests there is far more capacity in the North Atlantic climate system to produce wetter and more prolonged flood‐rich periods than hitherto experienced in the twenty‐first century. Looking forwards, an increased likelihood of weather extremes due to climate change means that geomorphological based flood series extensions must be placed at the centre of flood risk assessment in the UK uplands and in similar areas worldwide. Copyright © 2015 John Wiley & Sons, Ltd.